Preparation of nickel and cerium doped cobalt-based catalyst and application of nickel and cerium doped cobalt-based catalyst in catalytic decomposition of nitrous oxide
A co-precipitation method was used to prepare a cobalt-based catalyst co-doped with nickel and cerium, forming a spinel-type Co3O4 structure co-doped with Ni and Ce. This solved the problems of high reaction temperature and weak resistance to impurity interference in cobalt-based catalysts, and achieved low-temperature and high-efficiency decomposition of nitrous oxide and improved anti-interference performance.
Patent Information
- Application Number
- CN202511690643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-01-23
AI Technical Summary
Existing cobalt-based catalysts exhibit high reaction temperatures and weak resistance to impurity interference in the decomposition of nitrous oxide, and are particularly prone to deactivation in industrial exhaust gases containing impurity gases such as O2, H2O, and NO.
A co-precipitation method was used to prepare a cobalt-based catalyst co-doped with nickel and cerium, forming a spinel-type Co3O4 structure co-doped with Ni and Ce. This structure has a mesoporous structure and small particle size, which improves the activity and stability of the catalyst.
It significantly reduces the decomposition temperature of nitrous oxide to below 305℃, maintains a high conversion rate in complex industrial atmospheres, enhances anti-interference performance, and adapts to complex exhaust gas conditions.
Smart Images

Figure CN121372428A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of environmental protection catalytic materials and air pollution control technology, and particularly relates to a preparation method of a Co3O4 catalyst modified by nickel (Ni) and cerium (Ce) synergistic doping and application of the Co3O4 catalyst in a nitrogen monoxide (N2O) decomposition reaction, and is especially suitable for industrial tail gas purification in an environment containing O2, H2O, NO and other impurity gases. BACKGROUND
[0002] The information disclosed in this Background section is only for the purpose of increasing an understanding of the general background of the application and does not necessarily constitute an admission or a recognition that the information forms part of the prior art that is already known in any country in the world.
[0003] Nitrous oxide, also known as nitrous oxide, is a gas with strong greenhouse effect, and its global warming potential (GWP) is 310 times that of carbon dioxide (CO2) and 21 times that of methane (CH4). Due to its great impact on the environment, the harm of N2O is receiving more and more attention. In addition to strong greenhouse effect, N2O can exist in the troposphere for a long time due to its structural stability, and enter the stratosphere with air flow, causing serious damage to the ozone layer. At present, N2O has become one of the main substances causing the destruction of the ozone layer, and its destruction degree is increasing year by year.
[0004] At present, the main sources of N2O emission are agriculture and industry, and the industrial emission source is relatively controllable. In the industrial emission source, it mainly comes from industrial activities such as nitric acid production, adipic acid synthesis, coal chemical process and fossil fuel combustion. Among them, the N2O concentration in the tail gas of nitric acid plant can reach 5%-30%, and the N2O proportion in the tail gas of adipic acid production is even higher than 10%. With the expansion of global chemical industry scale, the N2O emission amount shows an increasing trend of 0.25% per year on average. Therefore, developing efficient N2O emission reduction technology has become an important issue.
[0005] At present, the main N2O emission reduction technologies for industrial tail gas include direct catalytic decomposition, thermal decomposition and selective catalytic reduction. The thermal decomposition method needs to operate at a high temperature of 800℃ or above, which has huge energy consumption and poor economic efficiency; although the selective catalytic reduction (such as using NH3 or CH4 as reducing agent) can reduce the reaction temperature, there are reducing agent consumption cost and by-product pollution risk. In comparison, the direct catalytic decomposition technology is considered as the most promising emission reduction scheme because of its simple process route, no need to add reducing agent, no secondary pollution and lower equipment investment. The core of this technology is the catalyst, which can reduce the activation energy of N-O bond breaking in N2O molecule, so as to greatly reduce the reaction temperature. Studies have shown that high-performance catalysts can reduce the N2O decomposition temperature to below 400℃, which can reduce the energy consumption by more than 50% compared with the thermal decomposition method.
[0006] The noble metal catalysts, with Ru, Rh, Pd, Pt as active components, supported on TiO2, Al2O3, etc. carriers, have the characteristics of excellent low-temperature activity and strong space velocity adaptability. The TiO2 supported noble metal catalyst (CN103157466B) developed by Dalian Institute of Chemical Physics, Chinese Academy of Sciences, has shown significant advantages in N2O decomposition reaction: the initial decomposition temperature can be reduced to below 200℃, and more than 90% conversion rate can be achieved in a wide concentration range. The catalyst uses anatase TiO2 as the carrier, and by controlling the size of noble metal nanoparticles (2-5 nm) and the concentration of surface oxygen vacancies, the adsorption-dissociation path of N2O is optimized. However, the large-scale application of noble metal catalysts is inevitably restricted by the cost bottleneck and poor resistance to sulfur poisoning. In the tail gas of nitric acid plant (containing trace SO2), the noble metal active center is easy to form stable compounds with sulfur and lose activity, and the regeneration is difficult and increases the maintenance cost.
[0007] The molecular sieve catalysts are endowed with catalytic activity by transition metal ion exchange (such as Co 2+ , Fe 2+ , Cu 2+ ). For example, the Cu / ZSM-5 catalyst (CN102380410A) uses the regular channels (pore size 5.5 Å) of ZSM-5 to realize the selective adsorption of N2O molecules, and the conversion rate of 1000 ppm concentration N2O can reach more than 95% in the range of 300-400℃. Its activity is derived from the efficient removal of O atoms in N2O by binuclear metal sites (such as [Cu-O-Cu] 2+ ), and the stabilizing effect of the molecular sieve framework on the reaction intermediates. However, the molecular sieve catalysts face serious challenges in the presence of water vapor: high-temperature water vapor (>10% concentration) will cause dealumination and channel collapse of the framework, leading to irreversible deactivation. The pilot data of a certain nitric acid plant shows that Cu / ZSM-5 has a more than 40% decrease in activity after continuous operation in tail gas containing 10% water vapor for 500 hours. In addition, nitrogen oxides in the tail gas will compete for the occupation of the molecular sieve acid sites, further reducing the N2O decomposition efficiency.
[0008] The metal oxide catalysts mainly use transition metal oxides (Co3O4, NiO, Fe2O3, etc.) as the main body, and improve the performance by doping with catalyst promoters and microstructure regulation, and have the advantages of cost and hydrothermal stability, becoming the most widely researched and applied system. Especially the cobalt-based catalyst, its spinel structure helps to improve the rate of N2O catalytic decomposition. For example, a kind of cobalt-based catalyst (patent number CN105289654A) is disclosed, which uses Co3O4 as the active component and cerium dioxide as the additive, and uses the impregnation method to prepare a catalyst, which has high N2O catalytic decomposition efficiency. However, due to the characteristics of its own structure, the cobalt-based catalyst has poor thermal stability, and in the presence of O2, H2O and NO impurities in the real tail gas, it is easy to lose activity.
[0009] The current N2O removal technology is direct catalytic decomposition, which is economical and efficient without adding reducing agent. However, the activity of the traditional catalyst in the actual atmosphere is insufficient, especially the interference of water vapor and O2, which leads to easy deactivation of the catalyst. Cobalt-based catalysts (such as Co3O4) have excellent redox performance and are widely studied non-noble metal catalysts, but there are still problems such as high reaction temperature and weak anti-interference ability. Based on the above situation, in combination with the industrial tail gas, in order to improve the catalytic performance, the dopant is introduced into Co3O4. Although single doping such as Ce or Ni can improve the activity to a certain extent, the synergistic doping is less studied, especially in reducing the reaction temperature and improving the anti-pollutant interference ability.
[0010] Therefore, it is of great practical significance to develop a nickel and cerium co-doped cobalt-based catalyst. SUMMARY
[0011] The application provides a nickel and cerium doped cobalt-based catalyst and its application in catalytic decomposition of nitrous oxide. The nickel and cerium doped cobalt-based catalyst has high activity, high stability and anti-poisoning performance.
[0012] The specific technical solutions are as follows: In a first aspect, the application provides a nickel and cerium doped cobalt-based catalyst, which is a Ni and Ce co-doped spinel type Co3O4 structure with a mesoporous structure, wherein the molar ratio of cobalt, nickel and cerium is 1:0.12:0.04.
[0013] The average particle size of the nickel and cerium doped cobalt-based catalyst is less than 9 nm.
[0014] The specific surface area of the nickel and cerium doped cobalt-based catalyst is greater than 100 m 2 / g.
[0015] In a second aspect, the application provides a preparation method of the nickel and cerium doped cobalt-based catalyst of the first aspect, which comprises: using a co-precipitation method, preparing a mixed solution of cobalt nitrate, nickel nitrate and cerium nitrate with a molar ratio of 1:0.12:0.04, adding sodium carbonate as a co-precipitation agent to the mixed solution, adjusting the pH of the mixed solution to 9 under stirring to co-precipitate and age, then washing, drying and calcining the precipitate at 300-400℃ in air atmosphere for 3 h to obtain the nickel and cerium doped cobalt-based catalyst.
[0016] The drying temperature is 100-130℃, and the drying time is 10-24 h.
[0017] In a third aspect, the present application provides a use of the nickel and cerium doped cobalt-based catalyst of the first aspect for catalytic decomposition of nitrous oxide in a polluted gas.
[0018] The use includes: catalytic decomposition of nitrous oxide in a polluted gas by using the nickel and cerium doped cobalt-based catalyst. The preparation method of the nickel and cerium doped cobalt-based catalyst includes: using a co-precipitation method, preparing a mixed solution of cobalt nitrate, nickel nitrate and cerium nitrate with a molar ratio of 1:0.12:0.04, adding sodium carbonate as a co-precipitation agent to the mixed solution, adjusting the pH of the mixed solution to 9 under stirring for co-precipitation and aging, then taking the precipitate for washing, drying and calcining at 300-400°C in air atmosphere for 3 hours to obtain the nickel and cerium doped cobalt-based catalyst.
[0019] The present application uses Co3O4 as an active component, dopes Ce and Ni, and uses a co-precipitation method to prepare a catalyst, which ensures high activity of the catalyst while still maintaining high conversion rate and anti-interference and revival performance in the environment of O2, H2O and NO.
[0020] The nickel and cerium doped cobalt-based catalyst is a Ni and Ce co-doped spinel type Co3O4 structure, has mesoporous structure, small particle size and high specific surface area. In a fixed bed reactor, the catalyst realizes high catalytic decomposition of nitrous oxide activity in the temperature range of 200-400°C, has strong anti-impurity interference and good thermal stability.
[0021] Further, the average particle size of the nickel and cerium doped cobalt-based catalyst is less than 9 nm.
[0022] Further, the specific surface area of the nickel and cerium doped cobalt-based catalyst is greater than 100 m 2 / g.
[0023] Further, the temperature of the catalytic decomposition is 100-750°C, for example, 150°C, 200°C, 250°C, 300°C, 325°C, 350°C, 375°C, 400°C, 425°C, 450°C, etc.
[0024] Further, the volume content of nitrous oxide in the polluted gas is 1000-3000 ppm, for example, 2000 ppm, etc.
[0025] Further, the polluted gas further contains one or more than two of oxygen, water vapor and nitric oxide.
[0026] Further, in the polluted gas, the oxygen content is 0-5 vol%, the water vapor content is 0-5 vol%, and the volume content of nitric oxide is 0-100 ppm.
[0027] Furthermore, the polluting gas contains oxygen with a content greater than 0 and not exceeding 5 vol%, and / or water vapor with a content greater than 0 and not exceeding 5 vol%, and / or nitric oxide with a volume content greater than 0 and not exceeding 100 ppm.
[0028] Furthermore, in the preparation method of the nickel and cerium-doped cobalt-based catalyst, the drying temperature is 100~130℃ and the drying time is 10~24 h.
[0029] Compared with the prior art, the beneficial effects of this invention are as follows: 1. Significantly reduces reaction temperature: Traditional Co3O4 catalysts typically require reaction temperatures above 400℃ to achieve high N2O decomposition rates. The Ni-Ce co-doped catalyst in this invention achieves N2O conversion rates exceeding 90% at 305℃, effectively reducing energy consumption.
[0030] 2. Enhanced anti-interference performance (resistant to O2, H2O, NO): In complex industrial atmospheres such as O2 (5 vol%), NO (100 ppm), and H2O (2 vol%), this catalyst still maintains a conversion rate of over 85%, and its resistance to toxicity is significantly better than that of undoped or single-doped catalysts. It is adaptable to complex exhaust gas conditions and is more suitable for industrial applications. Attached Figure Description
[0031] Figure 1 The graph shows a performance comparison of the catalysts prepared in Examples 2-6 and Comparative Example 1.
[0032] Figure 2 The graph shows a performance comparison of the catalysts prepared in Examples 1, 3, 7-9 and Comparative Example 1.
[0033] Figure 3 The images show the X-ray diffraction (XRD) patterns of the catalysts prepared in Examples 1, 3 and Comparative Example 1.
[0034] Figure 4 The graph shows the nitrogen adsorption-desorption test results of the catalysts prepared in Examples 1, 3 and Comparative Example 1.
[0035] Figure 5 The figure shows the transmission electron microscopy (TEM) particle size distribution of the catalyst prepared in Comparative Example 1.
[0036] Figure 6 The image shows the TEM particle size distribution of the catalyst prepared in Example 3.
[0037] Figure 7 The image shows the TEM particle size distribution of the catalyst prepared in Example 1.
[0038] Figure 8 Performance comparison chart of catalysts prepared in Example 1, Examples 10-11.
[0039] Figure 9 Performance comparison chart of catalysts prepared in Example 1, Examples 12-13.
[0040] Figure 10 Performance comparison chart of catalysts prepared in Example 1, Examples 14-15.
[0041] Figure 11 Performance test results chart of catalysts prepared in Example 16 and Comparative Example 2. DETAILED DESCRIPTION
[0042] The present application will be further described with reference to the following figures and examples. It should be understood that these examples are intended to illustrate the present application and are not intended to limit the scope of the present application. The methods of operation, if not otherwise indicated in the following examples, were generally carried out in accordance with conventional procedures or as recommended by the manufacturer.
[0043] Example 1: A catalyst S(1)-Ni for catalytic decomposition of nitrous oxide with water resistance and resistance to interference of impurity gases 0.12 Ce 0.04 Co: Take 4.3654 g of Co(NO3)2·6H2O, 0.5234 g of Ni(NO3)2·6H2O, and 0.2605 g of Ce(NO3)3·6H2O, and dissolve them in 200 mL of deionized water, and stir for 2 h. Use sodium carbonate as a coprecipitation agent, slowly drop 0.2 mol / L of sodium carbonate solution into the solution to adjust the pH of the solution, and titrate while stirring until the pH is 9. Then, age the solution overnight. The next day, perform suction filtration on the solution and the deposit, and wash the deposit with clean water while suction filtering until the pH of the filtrate is 7. Place the suction-filtered deposit in a blast drying oven for drying, with a drying temperature of 110°C and a drying time of 12 h, and then place the dried product in a muffle furnace for calcination in an air atmosphere, with a calcination temperature of 400°C and a calcination time of 3 h. After calcination, a black solid is obtained, which is tableted and ground, and the particle size is sieved to 40-60 mesh.
[0044] Performance testing of the catalyst for N2O decomposition: The residual N2O after catalytic decomposition was detected and quantitatively analyzed using a gas chromatograph equipped with a thermal conductivity detector (TCD). Hydrogen was used as the carrier gas, the injection port temperature was set to 130℃, the column oven temperature to 60℃, the TCD detector temperature to 120℃, and the current to 100 mA. The catalyst with a particle size of 40–60 mesh was loaded into a fixed-bed quartz tube at a loading of 0.3 g. During the test, the total gas flow rate was 100 mL / min, the N2O volume concentration in the feed gas was 2000 ppm, and the residual gas was argon.
[0045] Under the above reaction test conditions, such as Figure 2 As shown, the activity of the catalyst in Example 1 is the temperature (T) at which the N2O removal rate reaches 90%. 90 =305℃, and the complete decomposition temperature is 325℃.
[0046] Example 2: A catalyst S(2)-Ce for the catalytic decomposition of nitrous oxide 0.02 Co, referring to Example 1, without adding Ni(NO3)2·6H2O, but changing the amount of Ce(NO3)3·6H2O to make the molar ratio of Ce to Co 0.02:1, all other aspects are the same as in Example 1. Under the test conditions of Example 1, such as Figure 1 As shown, the activity of the catalyst in Example 2 is T. 90 =350℃, and the complete decomposition temperature is 375℃.
[0047] Example 3: A catalyst S(3)-Ce for the catalytic decomposition of nitrous oxide 0.04 Co, referring to Example 1, without adding Ni(NO3)2·6H2O, but changing the amount of Ce(NO3)3·6H2O to make the molar ratio of Ce to Co 0.04:1, all other aspects are the same as in Example 1. Under the test conditions of Example 1, such as Figure 1 , Figure 2 As shown, the activity of the catalyst in Example 3 is T. 90 =320℃, and the complete decomposition temperature is 340℃.
[0048] Example 4: A catalyst S(4)-Ce for the catalytic decomposition of nitrous oxide 0.06 Co, referring to Example 1, without adding Ni(NO3)2·6H2O, but changing the amount of Ce(NO3)3·6H2O to make the molar ratio of Ce to Co 0.06:1, all other aspects are the same as in Example 1. Under the test conditions of Example 1, such as Figure 1 As shown, the activity of the catalyst in Example 4 is T.90 = 330°C, complete decomposition temperature is 350°C.
[0049] Example 5: A catalyst S(5)-Ce for catalytic decomposition of nitrous oxide 0.08 Co, referring to Example 1, without adding Ni(NO3)2-6H2O, changing the amount of Ce(NO3)3-6H2O, so that the molar ratio of Ce and Co is 0.08:1, and the rest is the same as Example 1. Under the test conditions of Example 1, as shown in Table 1, the activity of Example 5 catalyst is T Figure 1 = 332°C, complete decomposition temperature is 350°C. 90 = 332°C, complete decomposition temperature is 350°C.
[0050] Example 6: A catalyst S(6)-Ce for catalytic decomposition of nitrous oxide 0.1 Co, referring to Example 1, without adding Ni(NO3)2-6H2O, changing the amount of Ce(NO3)3-6H2O, so that the molar ratio of Ce and Co is 0.1:1, and the rest is the same as Example 1. Under the test conditions of Example 1, as shown in Table 1, the activity of Example 5 catalyst is T Figure 1 = 333°C, complete decomposition temperature is 350°C. 90 = 333°C, complete decomposition temperature is 350°C.
[0051] Example 7: A catalyst S(7)-Ni for catalytic decomposition of nitrous oxide 0.04 Ce 0.04 Co, referring to Example 1, changing the amount of Ni(NO3)3-6H2O and Ce(NO3)3-6H2O, so that the molar ratio of Ni, Ce and Co is 0.04:0.04:1, and the rest is the same as Example 1. Under the test conditions of Example 1, as shown in Table 1, the activity of Example 6 catalyst is T Figure 2 = 320°C, complete decomposition temperature is 350°C. 90 = 320°C, complete decomposition temperature is 350°C.
[0052] Example 8: A catalyst S(8)-Ni for catalytic decomposition of nitrous oxide 0.08 Ce 0.04 Co, referring to Example 1, changing the amount of Ni(NO3)3-6H2O and Ce(NO3)3-6H2O, so that the molar ratio of Ni, Ce and Co is 0.08:0.04:1, and the rest is the same as Example 1. Under the test conditions of Example 1, as shown in Table 1, the activity of Example 6 catalyst is T Figure 2 = 325°C, complete decomposition temperature is 350°C. 90 = 325°C, complete decomposition temperature is 350°C.
[0053] Example 9: A catalyst S(9)-Ni for the catalytic decomposition of nitrous oxide 0.16 Ce 0.04 Co, referring to Example 1, but changing the amounts of Ni(NO3)3·6H2O and Ce(NO3)3·6H2O so that the molar ratio of Ni, Ce, and Co is 0.16:0.04:1, while all other aspects remain the same as in Example 1. Under the test conditions of Example 1, such as Figure 2 As shown, the activity of the catalyst in Example 6 is T. 90 =320℃, and the complete decomposition temperature is 340℃.
[0054] Comparative Example 1: Catalyst A(1)-Co3O4, referring to Example 1, without the addition of Ce(NO3)3·6H2O and Ni(NO3)3·6H2O, i.e., the molar ratio of Ni, Ce, and Co is 0:0:1, and all other aspects are the same as in Example 1. Under the test conditions of Example 1, such as Figure 1 , Figure 2 As shown, the activity of the catalyst in Comparative Example 1 is T. 90 =400℃, and the complete decomposition temperature is 425℃.
[0055] from Figure 2 It can be seen that a certain amount of Ni and Ce doping can significantly improve the performance of Co3O4 in catalytic decomposition of N2O, and the doping amount with a molar ratio of Ni:Ce:Co = 0.12:0.04:1 is the best.
[0056] Figure 3 The XRD test results of the catalysts prepared in Examples 1, 3, and Comparative Example 1 are shown. Figure 3 As can be seen, the diffraction peaks of the pure Co3O4 catalyst in Comparative Example 1 match the standard Co3O4 card (PDF#42-1467) in terms of diffraction angle, and no other impurity peaks were observed. The peaks located at 2θ = 19.0°, 31.3°, 36.9°, 44.8°, 59.4°, and 65.2° correspond to the (111), (220), (311), (400), (511), and (440) crystal planes of Co3O4, respectively. The XRD patterns of the catalysts in Examples 1 and 3 are similar to those of the pure Co3O4 catalyst in Comparative Example 1, with Ce... 0.04 Co and Ni 0.12 Ce 0.04 No Ce-related peaks were observed in the Co catalyst. Similarly, in the Ni catalyst... 0.12 Ce 0.04 No Ni-related diffraction peaks were observed in the Co catalyst. Furthermore, the Co3O4(311) peak shifted to 36.66° (a low-angle shift), which may be due to Ni...2+ Co3O4 lattice to replace Co 2+ .
[0057] We performed nitrogen adsorption-desorption tests on the catalysts prepared in Examples 1, 3 and Comparative Example 1, and the results are shown in Table 1. Figure 4 . Figure 4 The N2 adsorption-desorption isotherms and pore size distribution curves of Co3O4, Ce 0.04 Co and Ni 0.12 Ce 0.04 Co catalysts are shown in Figure 2. From the analysis of the nitrogen adsorption-desorption isotherms, it can be seen that all three catalysts exhibit type IV isotherms, and in the high P / Po region, they exhibit clear H1 hysteresis loops, indicating that the materials have highly uniform and regular mesoporous structures. The H1 hysteresis loops indicate that the catalysts have concentrated and unobstructed pore distributions, which is conducive to the rapid mass transfer of reaction gases and the release of products. In combination with the catalytic performance data of the three groups of catalysts, the Ni 0.12 Ce 0.04 Co catalyst exhibits the best catalytic activity in the N2O decomposition reaction due to its higher adsorption capacity and more perfect mesoporous structure, which provides more available active sites and efficient mass transfer channels.
[0058] The pore size distribution analysis results show that Co3O4, Ce 0.04 Co and Ni 0.12 Ce 0.04 Co catalysts all exhibit mesoporous structure characteristics to varying degrees, but there are significant differences. Among them, the pure Co3O4 sample has almost no obvious pore size distribution characteristics, and its structure is dense and its specific surface area is small, which limits the migration of reactants and the exposure of active centers; in contrast, the Ce 0.04 Co sample has a slightly wider pore size distribution and a relatively reduced mesoporous proportion, and its pore structure is improved compared to pure Co3O4, but its overall permeability and effective pore volume are still limited; however, the Ni 0.12 Ce 0.04 Co sample has a pore size mainly concentrated in the range of 3-5 nm, with a sharp distribution peak and the largest area, indicating that it has a highly ordered and uniform mesoporous structure, which is conducive to the rapid diffusion of reaction gases and the full exposure of active sites, thereby significantly improving the efficiency of the N2O decomposition reaction. In combination with the BET and XRD results, it can be seen that the specific surface area and pore volume of Co3O4 are low (58.84 m 2 / g, 0.27 cm 3 / g), and the grain size is large (14.9 nm), which limits the exposure of active sites. After the introduction of Ce, the specific surface area and pore volume of Ce 0.04 Co are significantly improved, and the grain size is reduced to 9.0 nm, indicating that Ce doping effectively inhibits grain growth and improves the pore structure. The Ni-Ce synergistic doped Ni0.12 Ce 0.04 Co further exhibited the highest specific surface area (105.03 m 2 / g) and the smallest crystallite size (8.6 nm), while maintaining good pore volume and smaller pore size, indicating that the synergistic effect significantly optimized the microstructure of the catalyst. These results show that Ce and Ni-Ce doping not only promotes the exposure of active sites, but also enhances the gas diffusion and oxygen migration ability, providing structural advantages for N2O decomposition reactions.
[0059] From Figure 5 , Figure 6 , Figure 7 are Co3O4, Ce 0.04 Co and Ni 0.12 Ce 0.04 Co three kinds of catalysts particle size distribution diagram, can see three kinds of catalyst particle size distribution, in which the particle size is in the range of 5-20 nm, but with Ce and Ni doping, the dispersion of particles has been improved, Ni 0.12 Ce 0.04 Co catalyst shows more uniform and smaller nanoparticles, mainly distributed in 6-11 nm.
[0060] Example 10: The difference from Example 1 is only that the pH of the solution is changed to 8, and the rest are the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Figure 8 .
[0061] Example 11: The difference from Example 1 is only that the pH of the solution is changed to 10, and the rest are the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Figure 8 .
[0062] Example 12: The difference from Example 1 is only that the calcination time is changed to 2 h, and the rest are the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Figure 9 .
[0063] Example 13: The difference from Example 1 is only that the calcination time is changed to 4 h, and the rest are the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Figure 9 .
[0064] Example 14: The difference from Example 1 is only that the calcination temperature is changed to 300°C, and the rest are the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Figure 10 .
[0065] Example 15: The difference from Example 1 is only that the calcination temperature is changed to 500°C, and the rest is the same. The obtained catalyst is tested according to the conditions of Example 1, and the results are shown in Table 1. Figure 10 .
[0066] Example 16: The catalyst of Example 1 is used, and the test conditions are changed. The performance and stability of the catalyst in the presence of impurity gases are tested. The test environment and test equipment are the same as those of Example 1. The catalyst raw gas concentration or content is as follows: N2O volume concentration 2000 ppm; NO volume concentration 100 ppm (if any); 2 vol% steam H2O (if any); 5 vol% O2 (if any); the rest is argon, and the total gas flow is 100 mL / min. The test temperature is 325°C. The test results are shown in Table 2. Figure 11 .
[0067] Comparative Example 2: The catalyst of Comparative Example 1 is used, and the test conditions are the same as those of Example 16. The test results are shown in Table 3. Figure 11 .
[0068] Figure 11 It is shown that the Ni 0.12 Ce 0.04 Co and Co3O4 catalysts have poor stability in a continuous interference atmosphere. As can be clearly seen from the figure, in the absence of interference gas (N2O volume concentration 2000 ppm, the rest is argon), the N2O conversion rate of Co3O4 at 325°C is only about 30%, and it rapidly drops to 4% after the introduction of 5 vol% O2. After the addition of 200 ppm NO and 2 vol% H2O, it is almost deactivated, indicating that its anti-interference ability is extremely weak. The Ni 0.12 Ce 0.04 Co catalyst modified by Ni and Ce has almost 100% N2O conversion rate at 325°C, showing extremely high activity. When 5 vol% O2, 200 ppm NO and 2 vol% H2O interference gases are continuously introduced, although the activity decreases (the minimum is about 43%), it is still significantly better than Co3O4, and after the interference components are cut off, its conversion rate can quickly rise to more than 90%, and finally stabilizes at about 94%. This phenomenon shows that the introduction of Ni and Ce not only effectively improves the ability of the catalyst to decompose N2O, but also enhances its resistance to reactive gases and recovery ability.
[0069] In conclusion, the catalyst of the application improves the activity of Co3O4 catalyst for the decomposition of nitrous oxide by the synergistic doping of nickel and cerium, reduces the reaction temperature required for the decomposition of nitrous oxide by the catalyst, and significantly improves the anti-interference performance of the catalyst in the complex working conditions coexisting with impurity gases such as NO and O2 and water vapor, and has good low-temperature decomposition of nitrous oxide and anti-interference ability in complex working conditions.
[0070] Furthermore, it is to be understood that even though numerous characteristics and embodiments of the application have been set forth in the foregoing disclosure, the exact character it be subjected to changes or modifications within the scope of the application as claimed.
Claims
1. A nickel and cerium doped cobalt-based catalyst, characterized in that, The nickel and cerium doped cobalt-based catalyst is a Ni and Ce co-doped spinel Co3O4 structure with mesoporous structure, wherein the molar ratio of cobalt, nickel and cerium is 1:0.12:0.
04.
2. The nickel and cerium doped cobalt-based catalyst of claim 1, wherein, The average particle size of the nickel and cerium doped cobalt-based catalyst is less than 9 nm.
3. The nickel and cerium doped cobalt-based catalyst of claim 1, wherein, The specific surface area of the nickel and cerium doped cobalt-based catalyst is greater than 100 m 2 / g.
4. The process for the preparation of a nickel and cerium doped cobalt-based catalyst according to any one of claims 1 to 3, characterized in that, The application further relates to a preparation method of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst.
5. The method of making a nickel and cerium doped cobalt-based catalyst according to claim 4, characterized in that, The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst.
7. Use according to claim 6, characterized in that, The application further relates to an application of the nickel and cerium doped cobalt-based catalyst.
8. Use according to claim 6, characterized in that, The application further relates to an application of the nickel and cerium doped cobalt-based catalyst.
9. Use according to claim 6, characterized in that, The application further relates to an application of the nickel and cerium doped cobalt-based catalyst.
10. Use according to claim 6, characterized in that, The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt-based catalyst. The application further relates to an application of the nickel and cerium doped cobalt
Citation Information
Patent Citations
Ferro-cobalt bimetallic catalyst for catalyzing nitrous oxide (N2O) decomposition
CN102380410A
Application of titanium oxide-supported noble metal catalyst in decomposition reaction of N2O
CN103157466B
Catalyst for catalytic decomposition of nitrous oxide and preparation method of catalyst
CN105289654A